2018
DOI: 10.1016/j.eplepsyres.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment with the GLP-1 analogue liraglutide alleviate chronic inflammation and mitochondrial stress induced by Status epilepticus

Abstract: Glucagon-like peptide-1(GLP-1) is a growth factor that has neuroprotective and anti-inflammatory properties. The protease resistant GLP-1 analogue liraglutide has been shown to be neuroprotective in previous studies in animal models of Alzheimer's disease or Parkinson's disease. Status epilepticus (SE) is a complex disorder, involving many underlying pathological processes, including excitotoxic and chronic inflammatory events. The present pilot study aims to investigate whether liraglutide alleviates the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…The GLP-1 receptor (GLP-1R) is widely expressed in neurons of several brain subregions such as hypothalamus, hippocampus, and cortex (Cork et al, 2015;Yoshino et al, 2015), suggesting the GLP-1 signaling could modulate a variety of neuronal functions (Korol et al, 2015;Prashant et al, 2018). Indeed, it has been reported that GLP-1 analogues exert neuroprotective effects in mouse models of acute and chronic epilepsy (Koshal et al, 2018;Wang et al, 2018;Hussein et al, 2019). Previous studies have shown that different apoptosis signaling pathways including BCL-2 associated X protein (BAX)/B cell lymphoma 2 (BCL-2) proteins are involved in seizure-induced neuronal death (Guo et al, 2017;Rubio et al, 2019), and liraglutide treatment could reduce the expression of an apoptotic marker caspase-3 in the brain of a Pentylenetetrazole (PTZ)-induced kindled rat model (Hussein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GLP-1 receptor (GLP-1R) is widely expressed in neurons of several brain subregions such as hypothalamus, hippocampus, and cortex (Cork et al, 2015;Yoshino et al, 2015), suggesting the GLP-1 signaling could modulate a variety of neuronal functions (Korol et al, 2015;Prashant et al, 2018). Indeed, it has been reported that GLP-1 analogues exert neuroprotective effects in mouse models of acute and chronic epilepsy (Koshal et al, 2018;Wang et al, 2018;Hussein et al, 2019). Previous studies have shown that different apoptosis signaling pathways including BCL-2 associated X protein (BAX)/B cell lymphoma 2 (BCL-2) proteins are involved in seizure-induced neuronal death (Guo et al, 2017;Rubio et al, 2019), and liraglutide treatment could reduce the expression of an apoptotic marker caspase-3 in the brain of a Pentylenetetrazole (PTZ)-induced kindled rat model (Hussein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 analogues can regulate mTOR expression via the AMPactivated protein kinase (AMPK) pathway (He et al, 2016;Zhang et al, 2017). Although several studies have shown the anticonvulsant potential of GLP-1 analogues (Koshal and Kumar, 2016;Wang et al, 2018;de Souza et al, 2019), the effect of liraglutide on the epileptogenesis and cognitive dysfunction in the DS mouse model has not been examined. In the present study, we investigated the possible anti-epileptic effect of liraglutide in Scn1a KO-induced epileptic mice and its potential effect on both Bcl-2 regulate apoptotic pathway and the mTOR pathway that are involved in epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the consequences of neonatal HI brain injury are not temporary, leading to neuropathies associated with the activation of neuroinflammatory processes. To our knowledge, liraglutide exerts a favorable anti-inflammatory effect in many animal models (McClean and Hölscher, 2014;Wang et al, 2018). The level of inflammatory cytokines at both the mRNA and protein levels can be used to evaluate the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that liraglutide exerts neuroprotective effects against injury and diseases of the nervous system, such as Alzheimer's disease (McClean et al, 2011;McClean and Hölscher, 2014), Parkinson's disease (Aviles-Olmos et al, 2014;Badawi et al, 2017), acute ischemic stroke (Yang et al, 2016;Dong et al, 2017), and traumatic brain injury (DellaValle et al, 2014;Hakon et al, 2015). A recently published study indicated that liraglutide could alleviate chronic inflammation and mitochondrial stress induced by status epilepticus (Wang et al, 2018). Thus, far, the specific mechanism through which liraglutide exerts its effects on neonatal HI brain injury remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Also examination of placental epigenetic machinery revealed sex differences [ 52 , 53 ]. In mice, female placental tissue has higher levels of global DNA methylation compared to male’s placentas, which likely provide females additional protection from dynamic changes in gene expression promoted by environmental insults [ 54 ]. Furthermore, rodent brain development begins during gestation but mostly continues postnatally.…”
Section: Discussionmentioning
confidence: 99%